Measured the concentrations of uranium in human blood samples from Iraq using CN-85 nuclear track detector - Rasheed, Essam (Journal of natural sciences, life and applied sciences, 2017)
The purpose of this study is to measure the concentration of uranium through 20 samples of human blood from healthy people and patients with leukemia, where the concentration of uranium increased by working in an unhealthy environment that led to people being exposed to cancer. The CN-85 was used to measure and determine alpha particles. Blood samples were dried and 0.5 g of each sample was obtained. The reagent was then bonded to a neutron stream using an (Am-Be) and 5 × 103 n.cm 2s-1 for seven consecutive days. The reagents were then scrapped with NaOH and 6.25 N for five hours. The intensity of the effect was measured by the optical microscope and compared with standard samples prepared in vitro. The increase in the proportion of uranium in the blood was caused by the military wars in 1991 and 2003 where the use of depleted uranium in the munitions and the war in abundance. The concentrations of uranium for healthy people ranged from (0.077 to 0.216 ppb), at a rate of (0.121 ppb). Patients ranged from (1,330-1.960 ppb) at a rate of (1.671 ppb). The acceptable value from ICRP is (0.810 ppb).
Keywords: nuclear trace detector; human; uranium concentration